Integration of Artificial Intelligence (AI) in Indonesian Language Learning to Improve Elementary School Students' Narrative Writing Skills - Ramdani Tanjung; Asep Nurjamin; Lina Nurwahidah; Lucky Rahayu Nurjamin; Ari Kartini (Papanda Publisher, 2026)
In the era of digital transformation, the integration of Artificial Intelligence (AI) in Indonesian language learning offers a strategic opportunity to revolutionize literacy skills, particularly narrative writing skills at the elementary school level. This study aims to analyze the role, implications, and effectiveness of AI technology in facilitating the creative process of narrative writing, while identifying significant benefits and fundamental challenges in its implementation. The research method used is a Systematic Literature Review (SLR). The analysis was conducted on 25 reputable scientific articles, both national and international, published between 2021 and 2026. Data was synthesized using a thematic approach to map trends in the use of AI technology in pedagogical contexts. The study results show that the use of Natural Language Processing (NLP)-based AI and adaptive learning systems positively contribute to four main aspects: (1) strengthening narrative structure, (2) linguistic accuracy, (3) stimulating creative ideas, and (4) increasing student learning independence. In addition to cognitive aspects, AI integration has been shown to increase students' intrinsic motivation and self-efficacy in composing stories. However, this study uncovers critical challenges including teachers' digital literacy gaps, the risk of technology dependency on students, and ethical issues related to the originality of work and data security. The conclusion of this study confirms that AI is not a substitute for the role of educators, but rather a pedagogical augmentation tool. The integration of AI in the Indonesian Language curriculum must be carried out in a planned, ethical manner, and prioritize harmonious collaboration between technological intelligence and the teacher's human touch to maintain the depth of meaning in language learning.